Advances in the Management of Sleep Disorders in Juvenile Myoclonic Epilepsy - Polina Moskaleva; Olga Shilkina; Natalia Shnayder; Ivan Artyukhov; Diana Dmitrenko; Elena Yuryeva (International Journal of Biomedicine, 2018)
Juvenile myoclonic epilepsy (JME) is a well-defined sub-syndrome of idiopathic generalized/genetic epilepsy, usually presenting in adolescence and characterized by myoclonic jerks, predominately in the arms, associated with tonic-clonic seizures and less often generalized absences. Although the evidence base for a relationship between JME and sleep disorders is weak, most experts regard sleep disorders as an actual comorbidity. This paper reviews the literature underpinning the development of sleep disorders in JME patients. Data that report associated causes of sleep problems in JME patients are discussed, as is the importance of counseling on lifestyle issues. Lastly, a practical approach to managing sleep disorders in young men and women with JME is summarized.